DAMPAK COVID-19 TERHADAP PENDAPATAN PEDAGANG-PEDAGANG KECIL DI KANTIN UNIVERSITAS INDO GLOBAL MANDIRI PALEMBANG - Cindi Pramita; Muhlisin Muhlisin; Nova Yanti Maleha (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
The emergence of the Coronavirus Disease 2019 (Covid 19) pandemic outbreak, various countries are making every effort to prevent the spread of coronavirus is expanding in the region. Social restrictions be it total lockdown or quarantine of many countries in the world. Policies taken by the Government with Large-Scale Social Restrictions (PSBB) will have a big impact on important sectors of the country, Some crucial areas are affected by the implementation of these social restrictions. The economic and educational fields are not affected by the implementation of the policy. This study uses a qualitative approach with primary data obtained from the first source. Distance Learning Policy conducted in lieu of face-to-face learning also impacts the income of traders in the UIGM campus canteen. They were forced to close and forced their loss of income from trading in the cafeteria.